Impacts of fire on SouthEast Asia tropical forests biodiversity: A review. - Syaufina, Lailan; Nuruddin, Ahmad Ainuddin (Asian Network for Scientific Information (ANSINET), 2011)
Forest fires have affected millions of hectares of tropical forests and other vegetation types annually. Over the past decades, the increase occurrence of fires has caused degradation of the tropical forest ecosystem and caused impacts to the environment. The objective of this paper was to review the impacts of the fires to the tropical forest ecosystem in Southeast Asia. Forest fires affect vegetation by suppressing certain species and promoting other species causing changes in vegetation structure and altering successional pattern. It also rejuvenate tropical pines. Fire causes reduction in soil macroorganism diversity and change soil bacterial composition. Knowledge of fire effects on biodiversity may benefit forest managers. Fire adaptive vegetation can be used as important species in rehabilitation of burned area.